Innovation divide in the world economy: China’s convergence towards the Triad - Kowalski, Arkadiusz Michał (Technological and Economic Development of Economy, 2022)
The objective of this article is to assess the dynamics of the innovation divide between China and the Triad, as well as to determine the factors that influence its evolution. The Triad consists of three economies traditionally dominating the world economy: the United States, the European Union, and Japan. The methodology involves the decomposition of the innovativeness of the economy into innovation capability, innovation position, and the relationship between them, which indicates the efficiency of the innovation system. The analysis of dynamic indexes and σ-convergence in all these components confirms that the global economy has been gradually losing clear polarization into innovation leaders, found among developed countries and innovation followers, which have traditionally been associated with developing nations. In addition to demonstrating fast improvement in the Summary Innovation Index of China towards the Triad, the paper has a clear contribution by showcasing China’s improvement through the decomposed factors of the innovativeness of the economy. In comparison with the Triad, China has a proportionally higher innovation position and efficiency of the innovation system and a lower level of innovation capacity. This demonstrates its dependence on external sources of innovation and international technology transfer, e.g. through foreign direct investments.First published online 09 June 2022